Comparative Study on the Quality of Friesian Holstein Frozen Semen Treated with Extender from Various Artificial Insemination Centre in Indonesia - Arifiantini, I; Yusuf, TL; D, Yanti (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
The aim of this research was to compare the quality of Friesian Holstein (FH) frozen semen bull using extender from various artificial center in Indonesia. Fifteen ejaculates from 3 FH bulls were collected using artificial vagina twice a week. Collected semen then evaluated macro and microscopically. Good quality semen diluted using 4 different extenders which was extender from artificial insemination center I (BIB I); II (BIB II); commercial extender Andromedâ (Minitab, Germany) based on Soya lecithin (KK) and tris egg yolk extender (TF), original receipt from Faculty of Veterinary Medicine, IPB. Extended semen then packed into minitub straws 0.3 ml with the concentration of 25 million sperm each. The straw then equilibrated at 4 oC for 4 hours, freeze in the liquid nitrogen vapor for 10 minutes and the stored in liquid nitrogen container -196oC. After 24 hours, semen then thawed at 37oC for 30 second. Percentage of sperm motility, live and morphology were observed on raw, diluted post equilibrated and post thaw semen respectively. The data were analyzed using statistical analysis system (SAS) 6.12 version. Result showed that diluted and after equilibrated semen diluted with BIB II extender was significantly lower (P<0.01) on the percentage of sperm motility than other extender. The highest percentage was KK extender (57.90%), BIB I (52.09%), TF (46.36%), and BIB II (26.09%). The influence of different extender on the percentage of live sperm was significantly different (P<0.05) after equilibration. BIB II showed the lowest percentage compare with other extender. After semen were thawed, percentage of live sperm shows highly significant different among extender (P<0.01). The highest percentage of live sperm was KK (72.76%), BIB I (69.77%), TF (64.05%), and BIB II (51.28%) respectively. The highest percentage of sperm abnormality was on KK extender (6.98%) and the lowest was on TF extender (4.78%). Based on the material of frozen semen calculation per straw, the most expensive straw was BIB I (Rp 1158.17); followed by KK (Rp 715.00); TF (Rp 671.35 ) and BIB II (Rp 653.52). In conclusion, this result indicate that KK extender has a good post thawed sperm quality with the moderate price. (Animal Production 7(3): 168-176 (2005) Key Words: Artificial Insemination, Thawing, Lecithin, Extender